Population dynamics of mantis shrimp Harpiosquilla harpax and Oratosquillina sp. in the waters south of Madura Island, Indonesia - Yenni Arista; ZAIRION; YUSLI WARDIATNO (Society for Indonesian Biodiversity, 2020)
Abstract. Ekalaturrahmah YAC, Zairon, Wardiatno Y. 2020. Population dynamics of mantis shrimp Harpiosquilla harpax and Oratosquillina sp. in the waters south of Madura Island, Indonesia. Biodiversitas 21: 1458-1466. Mantis shrimps are a potential fishery resource in Indonesia, but information about their population dynamics in the southern waters of Madura is limited. This study aimed to determine the population structure, growth, life span, and rate of exploitation for two taxa of mantis shrimp (Harpiosquilla harpax and Oratosquillina sp.). The research was conducted from September 2018 to February 2019 in the southern waters of Madura. The results showed that for H. harpax the majority of males caught ranged in length between 132.50 and 139.37 mm while the majority of females were between 153.45 and 160.22 mm. For Oratosquillina sp., the majority of males caught ranged from 84.70 and 89.60 mm while the majority of females were between 89.85 and 95.30 mm. The Growth Coefficient (K) for H. harpax was estimated to be 0.65 per year for males and 0.60 per year for females; while for Oratosquillina sp. the estimates were 0.81 and 0.78 per year, respectively. The L? value for H. harpax males was 183.00 mm and for females 250.55 mm, while the L? values for Oratosquillina sp. were 112.64 mm for males and 137.02 for females. The life span of H. harpax was estimated at 5 years, while for Oratosquillina sp. it was 4 years. The exploitation rate (E) for H. harpax males and females was 0.65 and 0.67 respectively, while for Oratosquillina sp. it was 0.54 and 0.58. These estimations indicated overexploitation of the resource, particularly in the case of H. harpax.